Miombo trees and mycorrhizae - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The miombo woodlands constitute the largest single biome in Tanzania. They cover about two-thirds of the country and extend 1000 miles southwards through Zambia and Mozambique into Zimbabwe, and westwards to Angola and Zaire. Important tree species...